Understanding organic solvent permeation during nanofiltration via electrical impedance spectroscopy (EIS) - Ng, Angie Qi Qi (2024)
To better understand organic solvent nanofiltration mechanisms, Electrical Impedance Spectroscopy was used to analyze real-time changes in the membrane, which functions as a variable dielectric and exhibits changes in capacitance as the solvent permeates. The 350 kDa membranes were composed of polydimethylsiloxane active layers atop polyacrylonitrile supports, while the two solvents were ethanol and isopropyl alcohol (IPA). Four key differences between the solvents are revealed. Firstly, the flux decline was greater for ethanol because the higher polarity promoted adsorption. Secondly, during filtration, the conductance decreased for ethanol but increased for IPA. Thirdly, increasing pressure increased the membrane thickness for ethanol but not for IPA. Fourthly, the permeation mechanisms vary between the two solvents at different pressures. At the lower initial flux, flux decrease was due to extensive adsorption for ethanol, but to the accumulation of IPA impeding permeation for IPA. For the higher initial flux, the gentler flux decline for ethanol was due to greater membrane swelling, whereas the steeper decline for IPA was due to the high driving force promoting permeation through the DP layer to the membrane substrate. The results here underscore the importance of membrane-solvent interactions in affecting OSN performance.